Predicting prolonged dose titration in patients starting warfarin. Issue 11 (26th July 2016) - Finkelman, Brian S.; French, Benjamin; Bershaw, Luanne; Brensinger, Colleen M.; Streiff, Michael B.; Epstein, Andrew E.; Kimmel, Stephen E.
Abstract: Purpose: Patients initiating warfarin therapy generally experience a dose‐titration period of weeks to months, during which time they are at higher risk of both thromboembolic and bleeding events. Accurate prediction of prolonged dose titration could help clinicians determine which patients might be better treated by alternative anticoagulants that, while more costly, do not require dose titration. Methods: A prediction model was derived in a prospective cohort of patients starting warfarin ( n  = 390), using Cox regression, and validated in an external cohort ( n  = 663) from a later time period. Prolonged dose titration was defined as a dose‐titration period >12 weeks. Predictor variables were selected using a modified best subsets algorithm, using leave‐one‐out cross‐validation to reduce overfitting. Results: The final model had five variables: warfarin indication, insurance status, number of doctor's visits in the previous year, smoking status, and heart failure. The area under the ROC curve (AUC) in the derivation cohort was 0.66 (95%CI 0.60, 0.74) using leave‐one‐out cross‐validation, but only 0.59 (95%CI 0.54, 0.64) in the external validation cohort, and varied across clinics. Including genetic factors in the model did not improve the area under the ROC curve (0.59; 95%CI 0.54, 0.65). Relative utility curves indicated that the model was unlikely to provide a clinically meaningful benefit compared with no prediction. Conclusions: Our results suggest that prolonged dose titration cannot be accurately predicted in warfarin patients using traditional clinical, social, and genetic predictors, and that accurate prediction will need to accommodate heterogeneities across clinical sites and over time. Copyright © 2016 John Wiley & Sons, Ltd.